Beyond MILF: Exploring Sexuality and Feminism in Public Motherhood - Friedman, May (Atlantis, 2014)
At first glance, the contemporary phenomenon of MILF (standing for “Mother I’d Like to Fuck”) in both pornography and popular culture seems to stand as an antidote for the desexualization of women who become mothers. Yet a more nuanced analysis of this archetype exposes the limitations of the genre and the ways that it serves to objectify women and reify normative views of motherhood. In particular, the term is deeply raced and classed. Through an analysis of three white middle-class mothers who perform in varying sites of popular culture, the MILF trope will be explored and critiqued. The three examples include Emily Maynard, star of The Bachelor (2011) and The Bachelorette (2012); Madison Young, feminist porn star, artist, and entrepreneur; and Kendra Holliday, blogger, sex activist, and social media celebrity. The specifics of each woman’s performances of public sexy motherhood are discussed with reference to dominant discourses of motherhood and sexuality, and particularly in relation to MILF.